Організаційно-правові та фінансові засади наукової діяльності в закладах вищої освіти МВС України: проблеми і шляхи вирішення з використанням математико-статистичної методології - Сербенюк, С. О.; Serbenyuk, S. O.; Надопта, Л. С.; Nadopta , L. S. (Право і безпека. – 2023. – № 3 (90). – С. 214-225, 2023)
Роботу присвячено проблемі вдосконалення чинного законодавства України, зокрема в галузі організації договірних наукових досліджень, фінансування наукової діяльності, а також апробації результатів цієї діяльності для подальшого впровадження в роботу підприємств, установ та організацій, що перебувають у підпорядкуванні Міністерства внутрішніх справ України. Проаналізовано чинну нормативно-правову базу із цієї проблематики. Приділено увагу основним практичним проблемам і запропоновано основні шляхи їх вирішення, враховуючи використання математичних розрахунків для встановлення критеріїв на основі запропонованих параметрів. Розглянуто статистику тенденцій розвитку публікаційної активності установ Міністерства внутрішніх справ України в базі даних Scopus.

The work is devoted to the problem of improving the current legislation of Ukraine, in particular, in the area of organisation of contractual scientific research, financing of scientific activities, and testing the results of these activities for further implementation in the work of enterprises, institutions and organisations subordinated to the Ministry of Internal Affairs of Ukraine. The current legal framework on this issue has been analysed. Attention has been paid to the main practical problems and the main ways of solving them have been proposed, taking into account the use of mathematical calculations to establish criteria based on the proposed parameters. The statistics of trends in the development of publication activity of the institutions of the Ministry of Internal Affairs of Ukraine in the Scopus database have been considered. Despite a significant number of domestic publications on the main directions of development and prospects of science in the system of the Ministry of Internal Affairs of Ukraine, the relevance of funding scientific activities, improving material and technical support, and social protection of researchers of higher education institutions of the Ministry of Internal Affairs of Ukraine has at most been merely mentioned among the problems of modern Ukrainian science. Regarding the research of foreign scholars in the field of mechanisms of organisation and financing of scientific activities, it can be noted that the most common type of funding is grants, and therefore most studies are devoted to grant applications and their impact, as well as the problems of filling the funding budget, innovations in equitable funding, etc. Thus, the central issue of this article has not been studied. The solutions to several problematic issues in this area have been proposed, including: introduction of a new funding mechanism, in particular, under the conditions of contractual research; organisation of special research competitions for institutions of the Ministry of Internal Affairs of Ukraine; creation of the Unified State Register of Scientific Research in the system of the Ministry of Internal Affairs of Ukraine; development of the online platform “Science in the MIA System” to allow customers to submit applications for research and development work, monitor data by potential contractors and hold a transparent competition; introduce a new mechanism for testing and obtaining acts of implementation in scientific activities. The ideas and proposals for the introduction of new organisational and legal frameworks for scientific research in the system of the Ministry of Internal Affairs of Ukraine are an attempt to introduce a practical mechanism for the rational and most productive use of the scientific potential of departmental institutions and establishments to ensure the security of the State, protection of human rights and freedoms, combating crime, maintaining public safety and order, applying positive foreign experience in these areas, as well as the creation of innovative methods and technologies that can compete with similar achievements in the international scientific space.

Работа посвящена проблеме усовершенствования действующего законодательства Украины, в частности в области организации договорных научных исследований, финансирования научной деятельности, а также апробации результатов этой деятельности для дальнейшего внедрения в работу предприятий, учреждений и организаций, находящихся в ведении Министерства внутренних дел Украины. Проанализирована действующая нормативно-правовая база по этой проблематике.
Organisational, legal and financial bases for scientific activity in higher education institutions of the Ministry of Internal Affairs of Ukraine: problems and solutions based on mathematical and statistical methodology
Keywords: науково-дослідна робота; науково-конструкторська робота; фінансування; статистичні дані; математичні розрахунки; організаційно-правові засади; заклади вищої освіти системи МВС України; research work; research and development work; funding; statistics; mathematical calculations; higher education institutions of the Ministry of Internal Affairs; научно-исследовательская работа; научно-конструкторская работа; финансирование; статистические данные; математические расчеты; организационно-правовые основы